The Effect of Women's Financial Self-Efficacy on Financial Product Ownership - Njo Anastasia; Mellicha Jeni Lestaritio (Universitas Hayam Wuruk Perbanas, 2020)
The government is intensively implementing formal and informal education to improve individual financial literacy. This study aims to examine the effect of women's financial self-efficacy on financial product ownership, controlling for contributing to financial literacy, financial risk preferences, and demographic factors. The sample consists of 253 female respondents who live in Surabaya and already have financial products. The data are collected using questionnaires and processed using binary logistic regression. The results show that women's financial self-efficacy significantly affects the choice of financial products in the form of investment, credit cards, and other loans. However, it does not significantly affect the choice of financial products in the form of savings, mortgages, health insurance, and life insurance. This study is expected to provide benefits in developing learning methods to appropriately improve women's financial literacy according to the available financial product choices. Besides, this study is also expected to provide advice to female clients to diversify their investment product portfolios according to their personalities to achieve their financial goals.